Tourists' value orientations, environmental concern and perception toward appropriate use of national parks / Seyed Ahmad Moumen Ghazvini - Ghazvini, Seyed Ahmad Moumen (2014)
Appropriate management and sound environmental planning is critical in natural-areas tourism. Natural-areas tourism can be an industry with low environmental impact and significant economic return, if properly planned and managed. In contrast, inadequate planned and managed natural-areas tourism will alter it to high environmental impact and limited economic return. Ecotourism is a sustainable form of natural-areas tourism which has increasingly grown throughout the world over the past decades. The primary aim of ecotourism relates to learning and experiencing nature and should contribute to the conservation of natural areas. In this matter; understanding of tourist attitudes and beliefs is crucial. These vary with people's values, attitudes, beliefs, awareness and environmental concern, as they become engaged in environmental issues and carry out pro-environmental behavior. Given the aforementioned reason, it is notably important to evaluate tourists' value orientations, environmental concern, and perception toward appropriate use of national parks which is useful for improving productive strategies in management of natural resources and protected areas. This study firstly attempted to examine value orientations and environmental concern among tourists along with their perception toward appropriate use of national parks and secondly investigated the relationship between abovementioned variables. A self-administrated questionnaire was collected from 379 tourists in Taman Negara, Pahang. A number of statistical analyses were applied with the purpose of achieving the research objectives as well as exposing the results of the study questions and hypotheses. The findings reveal that egoistic value orientation has negative relationship while altruistic value orientation and biospheric value orientation have positive relationship with environmental concern. Environmental concern also found out negatively related with four favorable constructs regarding appropriate use of national parks. The results show positive and negative relationship between three types of value orientations and accommodation and services, activities, and facilities within national parks. Moreover, the role of environmental concern as a mediator has been proven as it mediates the relationship between value orientations and appropriate use of national parks. The outcomes of this study theoretically contribute to the ecotourism literatures through presenting supplementary insights into value orientations and environmental concern of tourists and their perception regarding appropriate use of national parks. The results will also serve management of natural resources and national parks to put into practice the notion of use without abuse.